Analisis Faktor-Faktor Yang Mempengaruhi Minat Berwirausaha Santri Pondok Pesantren - Kamal, Al Haq; Thoyyibah, Nasirothut (At-Taqaddum, 2020)
This research is aimed to find out the factors such as the social media, surrounding, intelligence, personality, and individual motivation influenced to entrepreneurship interest of students of Al Munawwir Islamic boarding school, Q complex. This type of research is quantitative descriptive. Data sources in this research are primary data in questionary and secondary data likes the number of student and history of Al Munawwir Islamic boarding school, Q complex, Yogyakarta. Population in this research is female students Al Munawwir Islamic boarding school, Q complex, Yogyakarta. The Sample obtained with sampling quota technique that sample total is 63 students.The result indicate that the social media, intelligence, personality, and individual motivation have positive influence on the entrepreneurial interest of students. Only the environment doesn’t effect the student entrepreneurial interest in the Al Munawwir Islamic boarding school, Q complex, Yogyakarta.